Measles rubella campaign: coverage among slum children of Udupi municipality area in Karnataka - Kumar, Ashwini; Pai, Divya V.; Chaudhary, Aparna Sen; Ramireddy, Mahathi; Kamath, Asha (International Journal Of Community Medicine And Public Health, 2018)
Background: Poor coverage of measles vaccine and shift in the age of incidence of rubella towards adolescents and young adults with low rubella vaccination coverage leads to outbreaks of congenital rubella syndrome and measles in India. Therefore the Government of India has decided to administer measles rubella vaccine to all children from 9 months to 15 years of age in campaign mode to eliminate measles and control rubella. The aims and objectives of the study were to assess the coverage of measles rubella vaccination among the slum children of Udupi Municipality area following the MR campaign. Methods: A community based cross sectional study was conducted for a period of one month among parents of beneficiary children in 312 households of the study population. Results: Study targeted 350 families in 14 localities of which 312 families were covered consisting 578 children. Amongst them 560 (97%) were immunized and 28 (5%) of them had minor side effects. Fever (89%) was the most common side effect. Among those who were not vaccinated 18 (3%) nearly half of them (44%) were not aware of ongoing campaign and 22% as per physician’s advice. Conclusions: In the present study, coverage of MR vaccine was 97% and 88.1% (275) of the families studied knew about the MR campaign while only 267 (85.6%) actually received the MR vaccine.